2016
DOI: 10.1353/ken.2016.0004
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Effects and the Ethics of Therapeutic Communication: A Pragmatic Perspective

Abstract: In this article we explore the ethics of manipulating verbal information for the sake of influencing health outcomes through placebo and nocebo responses. Recent scientific research on placebo and nocebo effects has drawn attention to the ways in which communication by health professionals may modulate the symptoms of patients across an array of highly prevalent conditions such as pain, depression, anxiety, insomnia, irritable bowel syndrome, migraine, and Parkinson's disease. The positive and negative effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 62 publications
0
24
0
1
Order By: Relevance
“…However, the experts also acknowledged the current lack of knowledge about how best to provide this information to patients to ensure that patients are optimally informed. For example, there is insufficient knowledge about the ways in which patients and health-care providers can maximize placebo effects and minimize nocebo effects over time during repeated interactions and treatments [25]. …”
Section: Resultsmentioning
confidence: 99%
“…However, the experts also acknowledged the current lack of knowledge about how best to provide this information to patients to ensure that patients are optimally informed. For example, there is insufficient knowledge about the ways in which patients and health-care providers can maximize placebo effects and minimize nocebo effects over time during repeated interactions and treatments [25]. …”
Section: Resultsmentioning
confidence: 99%
“…It is known that the expectation of pain relief has been found to modulate the central regulation of pain through, in particular, the dopamine reward system and the endogenous opioid system (Price, Finniss, & Benedetti, 2008). There is also a growing body of evidence that in addition to what practitioners say, the way in which they deliver these messages (for example, with more or less empathy) can also affect health outcomes (Annoni & Miller, 2016; Caspi & Bootzin, 2002; Friedman, Sedler, Myers, & Benson, 1997). …”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Third, the positive suggestions often delivered alongside open-label placebos could involve an element of deception, depending on their wording. This is, strictly speaking, a distinct issue and we leave a discussion of the ethics of therapeutic communication to another study (Annoni & Miller, 2016). In short, the research demonstrating the effects and mechanisms of open-label placebos demands a reanalysis of ethical strictures on placebo use, and further discussion on how open-label placebos might be implemented is warranted.…”
Section: Ethical Implicationsmentioning
confidence: 99%
“…Doctor‐patient communication has therapeutic effects and holds power in promoting placebo responses or inhibiting nocebo responses . It has been shown that expectation plays a vital role in the placebo response, and medical providers serve as potent conditioning tools in guiding expectations .…”
Section: Study‐design Factors Impacting Placebo‐associated Improvementsmentioning
confidence: 99%
“…It has been shown that expectation plays a vital role in the placebo response, and medical providers serve as potent conditioning tools in guiding expectations . Variables, such as the environment in which the interaction takes place, clinical routines performed, and the type of medical instruments used (eg, stethoscope) may all influence outcomes . Other factors influencing placebo‐related improvements include altruism, empathy, and compassion on the part of the physician, in addition to validation and invalidation of a patient's symptoms …”
Section: Study‐design Factors Impacting Placebo‐associated Improvementsmentioning
confidence: 99%